Compendium of Abstracts of the 6th Philippine Computing Science Congress (PCSC 2006). - Saldana, Rafael P., Ph D. (Philippine Computing Journal)
A compendium of abstracts of the papers presented uring the 6th Philippine Computing Science Congress (PCSC 2006) held on March 28-29, 2006 at the Ateneo de Manila University is included in this paper. PCSC 2006 was organized by the Computing Society of the Philippines (CSP) and endorsed by the Commission on Higher Education (CHED).